Exploring the relationship between agility, flexibility, and dribble ability in football - Muhammad Feby Fakhriza; Purwono Sidik Permono (Sriwijaya Journal of Sport, 2025)
Research Problems: Dribbling is an important basic skill in soccer. Two physical components, agility and flexibility, are thought to influence dribbling ability. However, it is not clear which of the two contributes to this skill. Research Objectives: This study aims to analyze the relationship between agility, flexibility, and dribbling ability of Satria Kencana Serasi Academy players, Semarang Regency. Methods: The research used quantitative methods with Pearson correlation analysis and multiple regression through SPSS 25. The sample consisted of 19 players. Results: The results of Pearson analysis showed that there was a significant positive relationship between agility and dribbling ability (r = 0.516; p < 0.05), but there was no significant relationship between flexibility and dribbling ability (r = -0.124; p > 0.05). Multiple linear regression test showed that agility and flexibility simultaneously did not have a significant effect on dribbling ability (F = 2.993; p > 0.05). Conclusion: Agility is more dominant than flexibility in supporting dribbling ability. Therefore, coaches are advised to emphasize agility training more to improve players' dribbling skills.